Integration of Character Economy Education Through Digital Market Simulation in Social Studies Class of Muhammadiyah Mataram Senior High School - Edy Kurniawan; Farah Fadilla (Journal of Social Studies Education, 2025)
This study aims to analyze the integration of character-based economic education through the application of digital market simulation in Social Sciences (IPS) learning at SMA Muhammadiyah Mataram. The background of this research is based on the need to form a young generation that is not only capable in the cognitive aspect of economics, but also has character values such as honesty, responsibility, cooperation, and ethics in transacting in the digital era. This research approach uses a qualitative method with a case study design, which involves observation, in-depth interviews, and documentation of the learning process utilizing technology-based digital market simulations. The results of the study show that the integration of character values into the digital market simulation has a positive impact on improving students' economic literacy, critical thinking skills, and the formation of ethical entrepreneurial character. Project-based learning activities and online market simulations allow students to understand economic dynamics contextually, while instilling moral values in digital economy practices. This research emphasizes the importance of pedagogical innovation in social studies education that combines cognitive, affective, and psychomotor dimensions through a character-based digital approach. Thus, character economy education through digital market simulation becomes a learning model that is relevant to the demands of the 21st century and in line with the vision of strengthening the profile of Pancasila students in the Muhammadiyah school environment.